Influence of some soil characteristics to the current condition of populations of rare, endemic species Lonicera iliensis Pojark. (Experimental biology, 2016)
The article presents research data of natural populations of rare, endemic species of Lonicera iliensis Pojark. located along the river Ili, Chilik and Charyn. Determine the species composition of plant communities with Lonicera iliensis Pojark. and age structure of populations, as well as moisture and soil pH. If the analysis of the age structure of populations of medium generative individuals prevailed with 62.9% and 43.4% respectively in populations 1 and 3, in the 2 populations dominated by vegetative individuals 34.4%. Revealed that the soil pH has no significant effect to the age structure and projective cover of plants because the soil pH in all populations remained comparably the same level. Soil moisture in one population is quite high and amounted to 20,4-32,9%, however, due to the influence of anthropogenic factors are unfavorable conditions for the development of young and vegetative individuals. Therefore it is recommended to organize protection measures in the territory of 1 population. On 2 and 3 populations of soil moisture ranged 7,9-25,7 % and 13,8-18,8 %, accordingly the resumption of individuals in a natural way is fine.
Keywords: Lonicera iliensis Pojark.; Ili honeysuckles; rare and endemic species; soil moisture; soil pH